Unanchored Ubiquitin Chains, Revisited - Blount, Jessica R.; Johnson, Sean L.; Todi, Sokol V. (Frontiers in Cell and Developmental Biology, 2020)
The small modifier protein, ubiquitin, holds a special place in eukaryotic biology because of its myriad post-translational effects that control normal cellular processes and are implicated in various diseases. By being covalently conjugated onto other proteins, ubiquitin changes their interaction landscape - fostering new interactions as well as inhibiting others - and ultimately deciding the fate of its substrates and controlling pathways that span most cell physiology. Ubiquitin can be attached onto other proteins as a monomer or as a poly-ubiquitin chain of diverse structural topologies. Among the types of poly-ubiquitin species generated are ones detached from another substrate - comprising solely ubiquitin as their constituent - referred to as unanchored, or free chains. Considered to be toxic byproducts, these species have recently emerged to have specific physiological functions in immune pathways and during cell stress. Free chains also do not appear to be detrimental to multi-cellular organisms; they can be active members of the ubiquitination process, rather than corollary species awaiting disassembly into mono-ubiquitin. Here, we summarize past and recent studies on unanchored ubiquitin chains, paying special attention to their emerging roles as second messengers in several signaling pathways. These investigations paint complex and flexible outcomes for free ubiquitin chains, and present a revised model of unanchored poly-ubiquitin biology that is in need of additional investigation.